A new species of karst dwelling gecko (genus Cnemaspis Strauch 1887) from the border region of Thailand and Peninsular Malaysia - Grismer, L. Lee; Onn, Chan Kin; Nasir, Nurolhuda; Sumontha, Montri (Zootaxa, 2008)
A new species of karst dwelling gecko, Cnemaspis biocellata sp. nov. is described from the border region in the Satun Province of southern Thailand and the state of Perlis in northern Peninsular Malaysia. Cnemaspis biocellata sp. nov. is differentiated from all other species of Southeast Asian Cnemaspis by having a maximum SVL of 40.1 mm; 6–10 supralabials; 5–7 infralabials; weakly keeled scales on anterior portion of forearm; smooth ventral scales; no femoral pores; 8–12 precloacal pores; smooth subcaudals with an enlarged median row; one or two cloacal tubercles; 29–37 subdigital lamellae on fourth toe; no dark bands encircling tail; two distinct, white, well defined, occipital ocelli; a black occipital band bordering a series of closely spaced, large, white to yellow spots which form a nuchal band and a small, black shoulder patch enclosing a single white to yellow ocellus. This species is restricted to the karst formations of the Nakawan Range spanning the Thai-Malaysian border and has been misidentified as C. siamensis by previous authors.